Shear strength characteristics of mixing slag-stone ballast reinforcement with tire geo-scrap using large-scale direct shear tests - Morteza Esmaeili; Hamidreza Heydari; Maziar Mokhtari; Sara Darvishi (Railway Engineering Science)
Abstract Utilizing the ballast layer with more durable and stable characteristics can help avoid significant expenses due to decreased maintenance efforts. Strengthening the ballast layer with different types of reinforcements or substituting the stone aggregates with the appropriate granular materials could potentially help to achieve this goal by reducing the ballast deterioration. One of the exquisite and most effective solutions to eliminate these challenges is to use waste materials such as steel slag aggregates and useless tires. Utilizing these waste materials in the ballasted railway track will contribute to sustainable development, an eco-friendly system, and green infrastructure. So in a state-of-the-art insightful, the ballast aggregates, including a mixture of steel slag and stone aggregates, are reinforced with a novel kind of geo-grid made of waste tire strips known as geo-scraps. This laboratory research tried to explain the shear strength behavior of the introduced mixing slag-stone ballast reinforced with tire geo-scrap. To achieve this goal, a series of large-scale direct shear tests were performed on the ballast which is reinforced by tire geo-scrap and included various combinations of slag and stone aggregates. The concluded results indicate that the optimal mixing ratio is attained by a combination of 75% slag and 25% stone aggregates which is reinforced by tire geo-scrap at a placing level of 120 mm. In this case, the shear strength‌, internal friction angle, vertical displacement, and dilatancy angle of stone–slag ballast reinforced with geo-scraps exhibited average changes of + 28%, + 9%, − 28%, and − 15%, respectively.